Figures of Political Engagement in Palestine: Between the Rationality of Defeat and that of Liberation - Sbeih, Sbeih (PARTECIPAZIONE E CONFLITTO, 2025)
In the colonial context of Palestine, the field of political engagement has been shaped since its inception by two opposing rationales: a so-called ’rational and pragmatic’ logic, and a logic of ’revolutionary sacrifice’. The former, influenced by a balance of power favorable to the Zionist occupation and its Western allies, reflects a ’realist" approach that accepts the colonial condition, perceived as inescapable, and therefore only seeks to optimize its management. Here, defeat is internalized as material inferiority, legitimizing pragmatic efforts to improve Palestinian lives within the existing order. In contrast, the logic of revolutionary liberation rejects defeat as long as resistance persists, with armed struggle offering a unifying response to the fragmentation imposed on Palestine. This opposition reflects a struggle for legitimacy between two value systems and competing visions of the social world. This article analyzes this structural antagonism through two ideal type figures of political engagement in contemporary Palestine: the technocrat, embodying the rationality of homo economicus, and the revolutionary freedom fighter, the fida’yi, representing the rationality of homo libertatis. These competing rationalities and meanings of political commitment in turn relate to two different ’Palestines’: the ’Palestine of donors,’ where the "new Palestinian" invests in state-building; and the anti-colonial "free Palestine," where militants place their struggle in continuity with the liberation movement of the 1960s and 1970s. By tracing transformations in political engagement since the 1960s, the article reconstructs the rise of the technocrat, who has progressively overshadowed the sacrificial freedom fighter, before analyzing the latter’s recent resurgence.